2020
DOI: 10.12688/gatesopenres.13009.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot program for task sharing short and long-acting contraceptive methods in Burkina Faso

Abstract: The Family Health Directorate of the Ministry of Health and Background: Marie Stopes Burkina Faso, with implementing partners, Association Burkinabè pour le Bien-être Familial and Equilibres & Populations collaboratively conducted a pilot project in Burkina Faso focused on "increasing access to family planning (FP) services through task-sharing short-and long-acting family planning methods to primary care cadres." Four cadres of providers provided intrauterine devices (IUDs) and implants, while community healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 11 publications
(8 reference statements)
0
8
0
7
Order By: Relevance
“…The lack of significance in interaction terms between place of residence and education suggests that these variables did not undergo significant changes at the national level, and the differences between their categories remained largely unchanged. This stagnant inequality confirms the insufficient These findings are consistent with a recent study that revealed higher unmet contraceptive needs among rural women compared to urban women in Burkina [27]. The persistence of geographical barriers, such as limited access to mobile clinics and inadequate stock at certain locations, may contribute to the continued disparity between urban and rural areas [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lack of significance in interaction terms between place of residence and education suggests that these variables did not undergo significant changes at the national level, and the differences between their categories remained largely unchanged. This stagnant inequality confirms the insufficient These findings are consistent with a recent study that revealed higher unmet contraceptive needs among rural women compared to urban women in Burkina [27]. The persistence of geographical barriers, such as limited access to mobile clinics and inadequate stock at certain locations, may contribute to the continued disparity between urban and rural areas [10].…”
Section: Discussionsupporting
confidence: 89%
“…Unmet need has been examined using 2010 Demographic and Health Survey data [23], although it does not capture the percentage of women currently at risk of unintended pregnancy and not using contraception [24]. Recent research based on PMA2020 data has primarily focused on specific contraceptive methods [5] [25] [26] [27]. Most previous studies have investigated modern contraceptive use or unmet need among all women, regardless of their current risk of pregnancy.…”
Section: Studies Have Found Higher Contraceptive Use Among Christians...mentioning
confidence: 99%
“…From the analysis of studies ( 15 , 24 - 32 ) , three categories emerged: Nurse training to insert an intrauterine device; Nurses’ competency to insert an intrauterine device; and Women’s access to intrauterine devices.…”
Section: Resultsmentioning
confidence: 99%
“…The findings showed records of IUD insertion by nurses over 40 years ago ( 24 - 25 ) and, since then, different forms of training these professionals to perform the procedure have been documented ( 24 , 27 , 29 , 31 - 32 ) . A study carried out in 1979 described how nurses and midwives were trained to insert and remove IUD, in which each professional needed to insert 20 devices to be considered qualified ( 24 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation